Altitude-induced effects on muscular metabolic stress and hypertrophy-related factors after a resistance training session. Issue 8 (13th September 2020) - Feriche, Belen; Schoenfeld, Brad J.; Bonitch-Gongora, Juan; de la Fuente, Blanca; Almeida, Filipa; Argüelles, Javier; Benavente, Cristina; Padial, Paulino
Abstract: This study examined the acute effects of exposure to moderate altitude on factors associated with muscular adaptations following whole-body hypertrophy-oriented resistance training ( R T ) sessions. Thirteen resistance-trained males completed both counterbalanced standard hypertrophic R T sessions (3 sets × 10RM, 2 min rest) at moderate-altitude (H; 2320 m asl) and under normoxic conditions (N; <700 m asl). Participants rested 72 h between training sessions. Before and after the exercise session, blood samples were obtained for determination of metabolites and ions (lactate, inorganic phosphate, liquid carbon dioxide and calcium) and hormones (testosterone and growth hormone). Session-related performance and perception of effort (s-RPE) were also monitored. Results showed no meaningful differences in performance or s-RPE (8.5 ± 1.4 vs 8.6 ± 0.8 respectively for N and H; p  = 0.603). All blood variables displayed statistically significant changes throughout the recovery period compared to basal levels ( p  < 0.05), except for the testosterone. However, no altitude effect was observed in maximal blood lactate, calcium or anabolic hormones ( p  > 0.05). The reduction observed in the liquid carbon dioxide concentration in H (21.11 ± 1.46 vs 16.19 ± 1.61 mmol·l −1 ) seems compatible with an increase in buffering capacity. Compared to N, inorganic phosphate displayed lower recovery values after the R T in H (2.89 ± 0.64 vs 2.23 ± 0.60 mg dl −1 ; p  = 0.007). The results of this study do not support an accentuated effect of acute moderate terrestrial hypoxia on metabolic and hormonal factors linked to muscle growth during hypertrophic resistance training.